Are adolescents studying in private schools more obese? a comparative study among adolescents from different types of schools in Kerala, India - Varghese, Aby Dany; Mathew, Geethu; Benjamin, Anoop Ivan (International Journal of Contemporary Pediatrics, 2019)
Background: Adolescent obesity is a serious public health challenge of this century. It is associated with many factors including sleep patterns among adolescents. Methods: This cross-sectional study was conducted in Pathanamthitta district, Kerala. Adolescents studying in high school and higher secondary classes were included using stratified random sampling. Study tools included a structured questionnaire and anthropometric measurements. Results: 657 students were enrolled from Government, Government-aided and Private schools. The mean age of the participants was 15.09±1.33 years. The overall prevalence of overweight and obesity was 13.8% and 6.5% respectively. Students in private schools were found to have higher prevalence of overweight (17.8%) and obesity (9.8%) compared to Government-aided (15.3% and 5.4%) and Government schools (8% and 4.5%). Students with lesser sleep duration had higher BMI values. Factors such as higher age, family income, parental education, lack of regular physical activity were associated with obesity. Students with more siblings and family members had low BMI compared to others. Conclusions: High prevalence of overweight and obesity was observed among adolescents especially among private school students. Inadequate sleep duration was also found to be associated with obesity. Primary prevention approach aimed at spreading adequate awareness among students, parents and teachers should be practiced.